(untitled) (Iraqi Journal of Science, 2023)
Methotrexate (MTX)is a multiple therapeutic drug, it’s used in treatment of ectopic pregnancy, neoplastic disease, autoimmune disorders, and inflammatory conditions. It’s associated with a spectrum of side effect that includes damage to the (liver, kidney, lung and bone marrow). MTX has been associated with fetal malformations in( nervous, skeletal, gastrointestinal, and cardiac) system, and even fetal death. The study was conducted to test the effect of two doses of MTX (5and 10mg/kg) on the development of the mice liver during two gestational age (day11 and day 17) of pregnancy.18 healthy female mice were divided into three groups ,first group (control) was injected with normal saline ,second group injected with 5mg/kg and third group injected with 10mg/kg (all groups were injected on day 7 of gestation). Histology examination of control fetal liver on day11of gestation showed normal fetal development where cords of hepatoblast were formed and hepatic blood sinusoids were filled with erythroblasts ,fetal liver of animals dosed with 5mg/kg and 10mg/kg on day 11 of gestation showed ballooning degeneration with hepatoblast that have pyknotic nucleus .control fetal liver of day 17 of gestation showed normal hepatocyte arranged around a central vein, fetal liver of animals of day 17 of gestation dosed with 5mg/kg showed ballooning degeneration while fetal liver of 17 days of gestation dosed with 10mg/kg showed ballooning degeneration with inflammatory infiltration. Results of this study revealed that low dose MTX can affect internal organs causing damage during gestational age which might cause problems later in life after birth ,the effect have been proven in mice but does not necessarily apply on human but a possibility of such damage in human should be kept in mind.